Drew and Jot. 1, Dueling doodles - Baltazar, Art (KaBoom!, 2019)
Full-color graphic novel featuring fifth graders Drew and Foz who both like to draw comics and decide to create a comic book together. When Andrew's little sister draws a super alien into their story, Drew and Foz must work together to save their creation.